Organic Synaptic Diodes Based on Polymeric Mixed Ionic‐Electronic Conductors. (28th December 2021) - Gärisch, Fabian; Ligorio, Giovanni; Klein, Patrick; Forster, Michael; Scherf, Ullrich; List‐Kratochvil, Emil J. W.
Abstract: Neuromorphic devices are likely to be the next evolution of computing, allowing to implement machine learning within hardware components. In biological neural systems, learning and signal processing are achieved by communication between neurons through time‐dependent ion flux in the synapses. Integrating such ion‐mediated operating principles in neuromorphic devices can deliver an energy efficient and powerful technology. Here a device known as a light‐emitting electrochemical cell is revisited and modified, exploiting its ability to modulate current through ion accumulation/depletion at the electrodes and turn it into an organic synaptic diode. This two‐terminal device is based on an organic mixed ionic‐electronic conducting polymer that serves as active layer for conduction of lithium ions as well as charge carriers. The ionic conduction properties are modified by cryptand molecules, able to reversibly capture ions. The device can be reliably switched between states for at least 100 cycles and displays state retention for multiple minutes. The applicability for neuromorphic applications is further demonstrated by exploring frequency‐dependent plasticity and paired‐pulse facilitation behavior in the millisecond range. The polymeric nature, combined with the simple two‐terminal architecture of the presented neuromorphic device, opens up a range of possibilities regarding the fabrication of artificial neural networks. Abstract : An organic synaptic diode based on a mixed ionic‐electronic conducting polymer is presented. Here the device current is dynamically modulated through ion accumulation/depletion at the electrode interfaces. Intermixed cryptand molecules allow for mid‐term stabilization of the resulting device state. Neuromorphic functionality is demonstrated through pulse frequency dependence and paired‐pulse facilitation behavior.